The Impact of Tropical Vernacular Courtyard on Air Temperature Reduction The Case Study of Djaduk Ferianto's House - Nugroho, Agung Murti (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2023)
The study of contemporary architectural work incorporating vernacular tropical design strategies is still not widely done. Architect Eko Prawoto did a lot of design exploration to provide comfort through the inclusion of natural elements and the relationship between outer and inner space in his contemporary residential work. Vernacular courtyards in buildings are one of the passive design strategies for lowering the air temperature in Djaduk Ferianto's house. This paper aims to evaluate tropical elements and the performance of air temperature reduction through visual observation and thermal environmental measurements. Visual observation is conducted by observing building elements that meet tropical design criteria and indicators that continue with a conformity analysis. Measurement of thermal environments limited in air temperature and humidity followed by descriptive, evaluative, and comparative analysis of neutral temperature and the value of air temperature reduction. The study findings are as follows: first, the main criteria of tropical design elements in Eko Prawoto's work according to the value of highly appropriate are courtyard elements, building form, roofs, and natural shades. Second, the lowest average comfortable air temperature and the longest duration of comfortable conditions are found in the courtyard room, which is 28.7°C for 17 hours per day. Third, the most significant reduction in air temperature occurred in the courtyard, with an average of 1.4°C compared to the dining room (1°C) and bedrooms (0.6°C). Recommendations for improving courtyard performance are adjusting proportions, adding a roof, placing shade plants, and raising the courtyard enclosure.